Analyse des perceptions locales des aménagements forestiers participatifs au Bénin - C.P. Djogbenou; R. Glèlè Kakaï; O. Arouna; B. Sinsin (VertigO)
The present study analyzed the perceptions of forest management by the surrounding populations of the forests reserves under management in Benin according to some criteria like patterns of the forests reserves considered, the sociocultural groups and the educational levels of the populations. The Factorial Correspondence Analysis (FCA) performed on surveyed data related to the perception of 690 informants randomly chosen in 23 surrounding villages of forest reserves helped to analyse the link between various patterns of people and their perceptions. Results revealed that, on the whole, forest management is perceived by the local populations of the forests as a project in activity emphasizing the reforestation, employment for local people and a new manner of managing forest reserves. The local populations of forest reserves managed under projects PAMF and PGRN have perceptions based overall on forest repression (repression of the lack of civic virtue in the forest domain) and more means to forest agents in protecting forest reserves, those which took part in forest management with PRRF Project consider forest management as project in activity and finally the beneficiary populations of UNSO Project consider forest management as a new way to managing forests reserve. By considering the educational levels of people, results showed that the illiterate people have a traditional idea of forest management (reforestation, forest police) whereas those educated have a modern design of forest management (participatory approach of the populations, dialogue). These perceptions are visual and empirical and express the contents of the speeches of sensitization delivered by the projects in charge of the management of forest reserves.